Flood-spreading weirs to irrigation fields and pastures in Ethiopia - CGIAR Research Program on Water, Land and Ecosystems (2021)
Harnessing flash floods emerging from neighboring highlands helped convert degraded dry rangelands in Afar Region, Ethiopia, into productive land supporting diversified crop and fodder production. The practice is being scaled out in the dry lowlands of Somali and Oromia states.